2019
DOI: 10.1080/05704928.2019.1640719
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectrometric macronutrients review of soil health during taro crop production

Abstract: The purpose of this study was absorption spectrometric assessment the soil health of the soil from the taro growing areas of Taveuni, Fiji. The soil samples were collected in four cycles during taro cultivation period. The soil samples were analyzed for macronutrients (Ca, Mg, K, P and NO 3-N), soil organic matter (SOM) and soil pH. In general, the soil pH at all sites showed lower than the ideal pH (5.6-6.6) for taro planting throughout the cropping cycle. The results showed the significant loss in SOM from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Mean soil exchangeable calcium was low in this study (483.83 mg/kg) (Blakemore et al 1987). Similar low soil calcium concentrations have also been reported in soils of Fiji by Curtin et al (1991), Waterloo (1994), Morrison (2019) and Nisha and Prasad (2020). Acid soils are commonly associated with calcium deficiencies (Nisha and Prasad 2020).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Mean soil exchangeable calcium was low in this study (483.83 mg/kg) (Blakemore et al 1987). Similar low soil calcium concentrations have also been reported in soils of Fiji by Curtin et al (1991), Waterloo (1994), Morrison (2019) and Nisha and Prasad (2020). Acid soils are commonly associated with calcium deficiencies (Nisha and Prasad 2020).…”
Section: Discussionsupporting
confidence: 77%
“…Similar low soil calcium concentrations have also been reported in soils of Fiji by Curtin et al (1991), Waterloo (1994), Morrison (2019) and Nisha and Prasad (2020). Acid soils are commonly associated with calcium deficiencies (Nisha and Prasad 2020). Calcium is also considered one of the limiting nutrients in tropical forests (Bizuti et al 2018).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Research has shown that analysis of the spectral signature of the soil enables the estimation of texture, water and organic matter content, cation exchange capacity, and soil chemical attributes, such as total carbon, pH, and concentrations of nitrate, calcium, potassium, magnesium, and phosphorus (Jiang et al, 2017;Soriano-Disla et al, 2017;Mayrink et al, 2019;Nisha & Prasad, 2020;Pätzold et al, 2020). However, it is necessary to use appropriate spectral signature analysis techniques to estimate soil attributes from spectroscopic data (Pinheiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%